Orientation relationships between α‐zirconium and δ‐hydride within a hydride blister. Issue 2 (10th February 2017) - Kerr, David; Long, Fei; Domizzi, Gladys; Daymond, Mark R.
Abstract : Both the expected and an additional orientation relationship between α‐Zr and δ‐hydride in blistered zirconium alloys are explored through the reconstruction of the parent α‐Zr phase from electron backscatter diffraction maps of δ‐hydride. Abstract : Both the expected and an additional orientation relationship between α‐Zr and δ‐hydride in blistered zirconium alloys are explored through the reconstruction of the parent α‐Zr phase from electron backscatter diffraction maps of δ‐hydride. Parent and child variant relationships for the transformation are presented with the aim of reconstruction of the parent α‐Zr grain structure and texture from orientation maps of the δ‐hydride at varying distances from the blister centre in a recrystallized Zircaloy‐4 sample. Up to 13% of the δ‐hydride is found to be variants of the additional orientation relationship, the fraction of which decreases with increasing distance from the blister centre. Texture reconstructions by other experimental methods are accordingly suggested to incorporate the additional orientation relationship.